Indonesian EFL Students’ Experience towards Distance Learning during Covid-19 Pandemic - Noni Agustina; Putu Ayu Arya Windari; Made Wirawan (Siliwangi University, 2021)
Covid-19 pandemic has shifted face-to-face learning to distance learning since 2020. It occurs around the world including Indonesia. Generally, distance learning is new for the students but they have no choice to learn during this pandemic situation. Thus, this qualitative study aims to explore college students’ experience towards distance learning during Covid-19 pandemic. The college students taking English course at a Hindu Religion School located in Jakarta, Indonesia were administered a close and open-ended questionnaire and interviewed. The data were analyzed thematically. Findings suggested that the technology platform mostly used in the learning process was Zoom. In addition, most students did not find the obstacles to learning and only a few students had problems getting a stable internet access during learning. They also had adequate financial resources to undertake distance learning. They lacked time to study during the pandemic. Majority of them perceived that their language skills (speaking, reading, writing, listening, and vocabulary) were quite improved. They also reported that distance learning had positive and negative impacts. By comparing those impacts, they preferred distance learning to face-to-face learning in future. The recommendations for the instructors and policy makers are explicated to improve future learning better.